Integrin binding peptide promotes in vitro wound closure in the L929 mouse fibroblasts - Karaman, Ozan; Onak, Günnur; Demirci, Emine Afra; Kahraman, Emine (The European Research Journal, 2017)
Objective. Molecular basis of wound healing process needs to further examined to determine the effective individual biological cues. The objective of this study was to investigate the wound closure, proliferation, and viability of L929 fibroblast when cultured with different concentration of soluble RGD peptid.Methods. RGD peptide was synthesized manually on solid phase. The percentage of healed wound area for control, 0.5 mM, 1 mM, and 2 mM at each time points were analyzed by ImageJ. Cell proliferation and viability were assessed with MTT and live/ dead analysis, respectively.Results. The results of wound closure area showed that increased RGD peptide concentration in the culture improved cellular migration which enables significantly accelerated wound closure. However, RGD peptide did not dramatically augmented cell proliferation. In addition, cell viability results indicated that dead cell numbers did not critically influence by increasing the RGD peptide concentration in the culture.Conclusions. The present study showed that soluble integrin binding peptide accelerated the migration and wound closure rate of L929 fibroblasts. Delivery of soluble integrin binding peptides into the wound area may be considered as an alternative wound treatment technique in the near future after proofing the concept study with animal and clinical studies.